Chinese women business leaders : seven principles of leadership - Lee, Jean (Jean S. K.) (Elsevier Asian studies series., 2017)
Chinese Women Business Leaders - Seven Principles of Leadership includes seven women who represent the characteristics of ShEOs in the wave of Chinese economic reform. Their unique life stories are also reflections of changes in Chinese society. These women have each played a distinctive role In China's rapid emergence. Reform and opening up has brought more opportunities than ever before to Chinese women, though along with these opportunities come some questions and challenges. The fetters and shackles of tradition have been shattered. A path for self-actualization has opened up. Women in mainland China have experienced great changes, and struggled with conflicts between traditional heritage and modern values. Ever since reform and opening up in 1978, the rapid emergence of women in leadership roles in business has paralleled significant upheavals in the Chinese business landscape.